Flow measurement around a cylindrical body by attaching flexible plate: A PIV approach. (August 2018) - Yayla, Sedat; Teksin, Suleyman
Abstract: In this study, flow structures and downstream wake behind a flexible splitter plate attached to a circular cylinder have been qualitatively and quantitatively investigated at three different Reynolds numbers of 2500, 5000 and 7500. The Particle Image Velocimetry (PIV) technique was implemented to examine the flow field downstream of the bluff body in deep water. Laser sheet illuminated the region 5 mm below the top of the cylinder. All results were compared with a bare cylinder case to analyze differences in flow characteristics. Time-averaged velocity vector field, vorticity contours <ω>, turbulent kinetic energy, TKE, rms of streamwise, u rms, transverse, v rms velocity components were acquired and also frequency, f of vortex shedding was carried out using single point spectral analysis from PIV data to indicate flow structures. It was observed that the flexible splitter plate had a considerable effect on vortex shedding and fluctuations were prominently weakened by the use of control material. Highlights: The flow field is analyzed using PIV measurements. Turbulent kinetic energy is also analyzed. Vortex shedding was investigated using single point spectral analysis from PIV data to indicate flow structures.